OTOMATISASI SISTEM PENERANGAN DENGAN MENGGUNAKAN LED BERTENAGA SURYA - , ANDITA NOOR SHAFIRA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Alternatif energy is an energy that issued by scientist now, especially electrical enery. Solar energy is one of alternatif energy which is potential in Indonesia. Automatization of Lighting System Using LED Lamp with With Solar Cell is a new inovation which designed to automate the operation of the lights work and to perform optimization of the use of electrical energy. The use of Solar Cell and LED is expected to be more efficient and economical in the use of electrical energy so it can support our green technology in Indonesia. The design of the hardware consists of: solar cell as a power supply, device control and data processing in the form of minimum system Arduino Uno, the LCD monitor, light sensor LDR, LED Lamp, and Mosfet driver. Based on the results of testing and performance of this prototype, this prototype has worked well. On the sensor, when the sensor detects the presence of light, then the light will die and when the sensor does not detect the presence of light, then the light will glow.